Description of global innovative methods in developing the WHO Community Engagement Package. Issue 6 (7th June 2022) - Bayugo, Yolanda Vargas; Labarda, Meredith; Cruz, Jose Rene Bagani; Mier-Alpaño, Jana Deborah; Tiangco, Pauline Marie Padilla; Oyene, Ukam Ebe; Omoleke, Semeeh Akinwale; Ulitin, Allan; Ong Jr, Alberto; Fajardo, Marvinson See; Echavarria, Maria Isabel; Alger, Jackeline; et al.
Abstract : Objectives: Development of a Community Engagement Package composed of (1) database of community engagement (CE) experiences from different contexts, (2) CE learning package of lessons and tools presented as online modules, and (3) CE workshop package for identifying CE experiences to enrich the CE database and ensure regular update of learning resources. The package aims to guide practitioners to promote local action and enhance skills for CE. Setting and participants: The packages were co-created with diverse teams from WHO, Social Innovation in Health Initiative, UNICEF, community practitioners, and other partners providing synergistic contributions and bridging existing silos. Methods: The design process of the package was anchored on CE principles. Literature search was performed using standardised search terms through global and regional databases. Interviews with CE practitioners were also conducted. Results: A total of 356 cases were found to fit the inclusion criteria and proceeded to data extraction and thematic analysis. Themes were organised according to rationale, key points and insights, facilitators of CE and barriers to CE. Principles and standards of CE in various contexts served as a foundation for the CE learning package. The package comprises four modules organised by major themes such as mobilising communities, strengthening health systems, CE in health emergencies and CE as a driver for health equity. Conclusion: After pilot implementation, tools and resources were made available for training and continuous collection of novel CE lessons and experiences from diverse socio-geographical contexts.